Analysis of key categories in research in the context of choosing reengineering as a tool for innovation - Chupryna, Iu.; Aleksieienko, V.; Matveyev , V.; Polzikov , M. (Ways to Improve Construction Efficiency, 2024)
The analysis of key categories in research on reengineering as an innovative tool in modern business allows for the identification of main approaches and methods that help organizations adapt to dynamic market conditions. Business process reengineering (BPR) involves a radical rethinking and complete overhaul of a company’s core processes, which results in a significant improvement in aspects such as productivity, product quality, customer service, and cost optimization. Given the ongoing development of technologies and growing demands for efficiency, reengineering has become one of the key tools in innovation development strategies. Reengineering encompasses various categories that serve as key benchmarks for researchers and practitioners in this field. Among them, it is important to highlight categories such as innovativeness, which promotes the implementation of new approaches; systematics, which ensures the integrity and comprehensiveness of the change process; and efficiency, which allows achieving maximum results with minimal costs. Technological advancement plays a special role in reengineering, as the application of new technologies significantly expands the possibilities for process improvement, while risk and change management ensures stability and control throughout the transformation process. The implementation of reengineering enables organizations not only to maintain competitiveness but also to create new market positions. Modernizing business processes lays the foundation for the company’s growth in an unstable market. With the development of digital solutions, reengineering helps create an effective business model that meets the demands of the modern business environment. This approach not only ensures profitability growth and efficient resource utilization but also supports an innovative culture within the organization, which is essential for sustainable development. In general, business process reengineering can be seen as a fundamental tool for achieving long-term strategic goals. In the context of the modern economy, where high adaptability is mandatory, reengineering becomes a crucial factor that allows companies to withstand competitive pressure and create conditions for further innovation achievements.